Play to Purchase: Exploring Gamification and Visual Design Impact on Impulse Buying in M-Commerce - Aprilia, Rachel Winda; Alfansi, Lizar (PT FORMOSA CENDEKIA GLOBAL, 2024)
The rapid growth of the e-commerce sector has intensified competition among platforms, making the implementation of gamification strategies crucial for maintaining a dominant market position. This research investigates the interplay of gamification elements, visual design, immersion, and impulsive buying behavior in the context of Indonesian e-commerce platforms, given the heightened competition. Utilizing a survey with 348 valid responses, Structural Equation Modeling (SEM) in SmartPLS 4.0 was employed for analysis. The study reveals that gamification elements, particularly tangible rewards, positively influence user immersion, consequently mediating impulsive buying tendencies. This highlights the significant impact of gamification on consumer reactions and overall user experience, emphasizing its value in influencing consumer choices. The findings contribute to existing literature on gamification in e-commerce platforms using the S-O-R theory and provide insights into the link between user immersion and impulsive buying, offering valuable guidance for marketing strategies in this underexplored area.